2020
DOI: 10.1038/s41467-020-18234-w
|View full text |Cite
|
Sign up to set email alerts
|

A moonlighting role for enzymes of glycolysis in the co-localization of mitochondria and chloroplasts

Abstract: Glycolysis is one of the primordial pathways of metabolism, playing a pivotal role in energy metabolism and biosynthesis. Glycolytic enzymes are known to form transient multi-enzyme assemblies. Here we examine the wider protein-protein interactions of plant glycolytic enzymes and reveal a moonlighting role for specific glycolytic enzymes in mediating the co-localization of mitochondria and chloroplasts. Knockout mutation of phosphoglycerate mutase or enolase resulted in a significantly reduced association of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 70 publications
2
51
0
Order By: Relevance
“…The total percentage of FPN3-GFP signal that colocalized with the mitochondrial or plastid signal exceeds 100%, indicating that a portion of the colocalized signal overlaps. Previous reports have revealed the frequent colocalization of mitochondria and chloroplasts/plastids (Nelson et al, 2007;Oikawa et al, 2015;Sparkes, 2018;Zhang et al, 2020), which most likely explains the partially overlapping colocalization signal detected in our results. Overall, our data confirm the plastid localization of FPN3-GFP previously reported by Conte et al (2009) and provide further evidence that FPN3 is dual targeted to the mitochondria as well.…”
Section: Fpn3-gfp Is Targeted To Both the Mitochondria And The Plastids In Arabidopsissupporting
confidence: 76%
See 1 more Smart Citation
“…The total percentage of FPN3-GFP signal that colocalized with the mitochondrial or plastid signal exceeds 100%, indicating that a portion of the colocalized signal overlaps. Previous reports have revealed the frequent colocalization of mitochondria and chloroplasts/plastids (Nelson et al, 2007;Oikawa et al, 2015;Sparkes, 2018;Zhang et al, 2020), which most likely explains the partially overlapping colocalization signal detected in our results. Overall, our data confirm the plastid localization of FPN3-GFP previously reported by Conte et al (2009) and provide further evidence that FPN3 is dual targeted to the mitochondria as well.…”
Section: Fpn3-gfp Is Targeted To Both the Mitochondria And The Plastids In Arabidopsissupporting
confidence: 76%
“…Here, we observed that FPN3‐GFP is colocalized with mitochondrial and plastid markers in stable transgenic lines (Figure 7a,b). As mitochondria and chloroplasts/plastids are frequently observed to colocalize (Nelson et al, 2007; Oikawa et al, 2015; Sparkes, 2018; Zhang et al, 2020), mitochondrial localization may not have been previously detected because of the high density of chloroplasts in the protoplasts imaged by Conte et al , (2009). Moreover, our study reveals that iron accumulates in both mitochondria and chloroplasts of fpn3 (Figure 7c,d).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al indicate that the phosphoglycerate mutase-enolase-pyruvate kinase interacts with voltage-dependent anion channel protein (VDAC1) of the outer mitochondrial membrane and the triose phosphate translocator of the chloroplast, and the interaction is considerably more efficient than the free enzymes of the extra-plastidial preparation, as well as prevents the use of substrate by competing reactions such as phosphoenolpyruvate carboxylase and amino acid biosynthesis in the plant. And lacking enolase compromised the movement of their mitochondria as well as the degree of mitochondria-chloroplast colocalization, so that the interaction of enolase with mutase/pyruvate kinase are important for promoting a highly efficient coordination of the major energy systems of the plant cell (77). However, mitochondrial ENO1 interacting with VDAC1 prevents Ca 2+ -induced loss of mitochondrial transmembrane potential, swelling of matrix and release of cytochrome c to regulate cardiomyocyte apoptosis, a critical regulator of the mitochondrial cell death pathway in the mammalian cells (78).…”
Section: Hypoxia-induced Eno1 Expressionmentioning
confidence: 99%
“…Moonlighting proteins have been reported to exhibit multiple functions, profoundly affected by their cellular localization and environmental stimuli. Here, we have reported, on the left, the well-known and original functions carried oud by (1) IDO1, (2) c-FLIP, (3) STAT3, (4) HSP, (5) HDAC, (6) STING, (7) Tgase2, (8) GAPDH, (9) CRT, (10) Cytc, (11) Cldn, and (12) HMGB1. On the right, some of the apparently unrelated functions mediated by the same proteins have shown.…”
Section: Indoleamine 23-dioxygenasementioning
confidence: 99%
“…Moreover, multifunction proteins might represent an original mechanism exploited by cells to overcome their limited amount of genomic information (5). Many reports have demonstrated that moonlighting proteins use their canonical biology and binding sites for carrying out their unexpected activities (5)(6)(7). However, emerging studies have unveiled also the presence of different active structure domains responsible for the induction of non-canonical activities (8) especially during pathological condition such as in cancer setting (9).…”
Section: Introductionmentioning
confidence: 99%